A cluster-randomized trial of client and provider-directed financial interventions to align incentives with appropriate case management in retail medicine outlets: Results of the TESTsmART Trial in western Kenya. - Jeremiah Laktabai; Emmah Kimachas; Joseph Kipkoech; Diana Menya; David Arthur; Yunji Zhou; Tabitha Chepkwony; Lucy Abel; Emily Robie; Mark Amunga; George Ambani; Meley Woldeghebriel; et al. (Public Library of Science (PLoS), 2024)
ACTs are responsible for a substantial proportion of the global reduction in malaria mortality over the last ten years, made possible by publicly-funded subsidies making these drugs accessible and affordable in the private sector. However, inexpensive ACTs available in retail outlets have contributed substantially to overconsumption. We test an innovative, scalable strategy to target ACT-subsidies to clients with a confirmatory diagnosis. We supported malaria testing(mRDTs) in 39 medicine outlets in western Kenya, randomized to three study arms; control arm offering subsidized mRDT testing (0.4USD), client-directed intervention where all clients who received a positive RDT at the outlet were eligible for a free (fully-subsidized) ACT, and a combined client and provider directed intervention where clients with a positive RDT were eligible for free ACT and outlets received 0.1USD for every RDT performed. Our primary outcome was the proportion of ACT dispensed to individuals with a positive diagnostic test. Secondary outcomes included proportion of clients tested at the outlet and adherence to diagnostic test results. 43% of clients chose to test at the outlet. Test results informed treatment decisions, resulting in targeting of ACTs to confirmed malaria cases- 25.3% of test-negative clients purchased an ACT compared to 75% of untested clients. Client-directed and client+provider-directed interventions did not offer further improvements, compared to the control arm, in testing rates(RD = 0.09, 95%CI:-0.08,0.26) or dispensing of ACTs to test-positive clients(RD = 0.01,95% CI:-0.14, 0.16). Clients were often unaware of the price they paid for the ACT leading to uncertainty in whether the ACT subsidy was passed on to the client. This uncertainty undermines our ability to definitively conclude that client-directed subsidies are not effective for improving testing and appropriate treatment. We conclude that mRDTs could reduce ACT overconsumption in the private retail sector, but incentive structures are difficult to scale and their value to private providers is uncertain. Trial registration: ClinicalTrials.gov NCT04428307.